Budgetary forecasts in Europe - the track record of stability and convergence programmes - Rolf Strauch; Mark Hallerberg; Jürgen von Hagen (European Central Bank (ECB), 2004)
We analyse the performance of budgetary and growth forecasts of all stability and convergence programmes submitted by EU member states over the last decade. Differences emerge for the bias in budgetary projections across countries. As a second step we explore whether economic, political and institutional factors can explain this pattern. Our analysis indicates that the cyclical position and the form of fiscal governance are major determinants of forecast biases. Projected changes in the budgetary position are mainly affected by the cycle, the need of convergence before EMU and by electoral cycles.
Keywords: C53; E17; H62; 330; budget processes; Fiscal forecasting; forecast evaluation; Stability and Growth Pact